Implementasi Sistem Pelayanan Kesehatan Berbasis Online Menggunakan Codeigniter 3 dan Metode MVC - Mario Maryanto Bani (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
Community Health Centers (Puskesmas) serve as the frontline for basic healthcare services for the community. However, the services at Waimangura Community Health Center are not yet fully optimal due to several obstacles, particularly in patient data recording, which is essential for registering every individual who visits for health check-ups, registration, and medical record management. Therefore, an information technology-based system is needed to enhance the effectiveness and efficiency of services. This research aims to implement a healthcare service system at Waimangura Community Health Center using the CodeIgniter 3 framework by applying the MVC (Model, View, Controller) method. The MVC method was chosen because it can separate application logic, display, and data management, making the system more structured, easier to develop, and maintaining consistency. The research stages include needs analysis, system design, implementation, and testing. The implementation results show that the built system is capable of assisting officers in patient registration, medical record data management, and information services. Patients also benefit from more transparent and efficient services. Based on the trial results, the system operates according to user needs and can improve the quality of healthcare services at the Waimangura Community Health Center. Thus, the implementation of CodeIgniter 3 with the MVC method has proven effective in building a structured, easily maintainable healthcare service system that can be further developed to support digital-based healthcare services.